Pengaruh Penggunaan Stick Pengendalian Hama Oryctes rhinoceros L. terhadap Produktivitas Tenaga Kerja - Yuliyanto . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
The horn beetle (Oryctes rhinoceros L.) bore oil palm shoots which resulted in inhibition of growth and destruction of the growing point so that the plant is deadly. Oryctes rhinoceros attack control is usually done manually with a lot of manpower required. One of the tools of controlling pests Oryctes rhinoceros is using a stick. This study aims to compare the work performance of manbosulfan application manually with stick. This research was conducted from March to May 2017 using observation method and application of stick tool design result. The research was conducted at PT Kayung Agro Lestari, Matan Hilir Utara, Ketapang, West Kalimantan. Research begins by designing a tool stick and making tool stick. Sticker tool made used for control of Oryctes rhinoceros. Application of active ingredients by using sticks can be more easily done on plants than manually, and plant height that is not uniform can be overcome with tool sticks that can be arranged in short length. Based on result of research, achievement of worker by using stick more efficient equal to 7,8 ha/HK compared to manual method 3 ha/HK.